The effect of price and promotion on distributor purchase interest in ZA Plus Fertilizer PT Petrokimia Gresik - Gynastiar, Khotib (Proceeding of International Management Conference and Progressive Papers, 2024)
This research was conducted with the aim of knowing whether there is an effect of price and promotion on distributor buying interest in PT Petrokimia Gresik’s ZA Plus Fertilizer products. The type of research used in this research is explanatory research using a quantitative approach. This study used non probability sampling technique with a sample size of 51 respondents. The results of this study indicate that the price variable has no effect on buying interest. while the promotion variable has a significant effect on distributor buying interest. This research was only conducted on ZA Plus Fertilizer products so that it cannot be generalized to other products. This research can be used as a reference for other researchers for further research.